2015
DOI: 10.1093/annonc/mdv315
|View full text |Cite|
|
Sign up to set email alerts
|

Sunitinib administered on 2/1 schedule in patients with metastatic renal cell carcinoma: the RAINBOW analysis

Abstract: mRCC patients who moved to a modified 2/1 schedule of sunitinib experience an improved safety profile compared with that observed during the initial 4/2 schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 21 publications
4
65
0
4
Order By: Relevance
“…To balance the clinical benefit with the toxicity of these agents, alternative ways to deliver these drugs have also been evaluated. A retrospective analysis (RAINBOW) reported by Bracarda et al evaluated 208 consecutive patients with previously untreated mRCC who started sunitinib on a 4/2 schedule, switched to a 2‐weeks‐on/1‐week‐off (2/1) schedule for toxicity, and used a second group of 211 patients who were treated on the 4/2 schedule for external control. In the group that changed from the 4/2 to the 2/1 schedule, grade 3 and 4 AEs were significantly reduced from 45.7% to 8.2% ( P < .001) after switching to the 2/1, including fatigue, hypertension, hand‐foot syndrome, and thrombocytopenia.…”
Section: Systemic Therapy For Metastatic Diseasementioning
confidence: 99%
“…To balance the clinical benefit with the toxicity of these agents, alternative ways to deliver these drugs have also been evaluated. A retrospective analysis (RAINBOW) reported by Bracarda et al evaluated 208 consecutive patients with previously untreated mRCC who started sunitinib on a 4/2 schedule, switched to a 2‐weeks‐on/1‐week‐off (2/1) schedule for toxicity, and used a second group of 211 patients who were treated on the 4/2 schedule for external control. In the group that changed from the 4/2 to the 2/1 schedule, grade 3 and 4 AEs were significantly reduced from 45.7% to 8.2% ( P < .001) after switching to the 2/1, including fatigue, hypertension, hand‐foot syndrome, and thrombocytopenia.…”
Section: Systemic Therapy For Metastatic Diseasementioning
confidence: 99%
“…[20][21][22][23][24] Three ongoing prospective studies (NCT02060370, NCT02689167, and NCT02398552) will further evaluate the value of the two/ one schedule. It is important to note that based on the dose/schedule distribution (Table 1) in our individualization study, the two/ one schedule was optimal in only 39 (37%) patients.…”
Section: Changing the Schedule From Four/two To Two/one May Not Optimmentioning
confidence: 99%
“…The results of this trial demonstrated better toxicity profile and better compliance with the 2/1 schedule 36. A retrospective analysis with 249 patients concluded with similar results 37. Even though this scheme has not been evaluated in GIST patients, it could be considered in some patients with poor tolerance to the conventional schedule 38…”
Section: Development Of Sunitinib In Gist: From Bench To Bedsidementioning
confidence: 55%